THE EFFECT OF CARBON EMISSION DISCLOSURE, RETURN ON INVESTMENT, AND ENVIRONMENTAL PERFORMANCE ON THE RETURN OF COMPANY SHARES IN THE INDONESIAN ENERGY SECTOR FOR THE 2019-2024 PERIOD - Muhammad Fikri Akbar; Rico Nur Ilham; Ristati; Nurlela (PT. Radja Intercontinental Publishing, 2025)
This study aims to analyze the effect of carbon emission disclosure, return on investment, and environmental performance on the return of company shares in the Indonesian energy sector periode 2019-2024. The research data can be accessed through the official website www.idx.co.id The sample in the study is as many as 12 energy sector companies with purposive sampling techniques. The data analysis tool in this study uses the panel data regression method with the Eviews 12 application tool with the selected Random Effect Model (REM) model. The results of the study found that carbon emission disclosure has a positive and significant effect on stock returns, return on investment has a positive and significant effect on stock returns, and environmental performance has a negative and insignificant effect on stock returns in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2024 period.